Transfer Reagents 4: Retro-Diels–Alder Routes to 3,6-Di(2-pyridyl)pyridazinonorbornadiene, a Test Bed for the Relative Dienofugacity of Isobenzofuran, Isoindole, and Anthracene - Margetić, Davor; Butler, Douglas N.; Warrener, Ronald N. (Synlett, 2013)
Norbornadiene cycloadducts reacted with 3,6-di(2-pyridyl)-s-tetrazine to produce pyridazines (diene-protected alkenes), following dehydrogenation (by DDQ) of the intermediate dihydropyridazines. The title 3,6-di(2-pyridyl)-pyridazinonorbornadiene was produced under flash vacuum pyrolysis conditions by ejection of anthracene (590 °C), isobenzofuran (630 °C) or isoindole (580 °C) from the corresponding pyridazines, establishing the following dienofugacity order: isoindole > anthracene > isobenzofuran. Calculations of the respective retro-Diels–alder activation energies at the B3LYP/6-31G* level of theory correctly predicted the experimentally found isobenzofuran > anthracene > isoindole order. Cavity bis-3,6-di(2-pyridyl)-pyridazine (dppn) and chevron-shaped bis-dppn ligands were prepared from the title compound by coupling at the norbornene π-bond.
Keywords: cycloadditions; heterocycles; ligands; flash pyrolysis; alkenes